2011
DOI: 10.1111/j.1526-4610.2011.01860.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Study of Telcagepant Plus Ibuprofen or Acetaminophen in Migraine

Abstract: The combination of telcagepant 280 mg with either ibuprofen 400 mg or acetaminophen 1000 mg did not show a statistically significant difference from telcagepant alone. Numerically greater treatment effects in the combination treatment groups over the telcagepant 280 mg monotherapy suggest that telcagepant combination treatments may merit further evaluation in studies powered to detect smaller additive benefits. (Clinicaltrials.gov; NCT00758836).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
1
26
0
1
Order By: Relevance
“…Another Phase II randomized, double-blind, placebocontrolled trial evaluated the efficacy and tolerability of telcagepant when co-administered with ibuprofen or acetaminophen (paracetamol) for the acute treatment of migraine [93]. The trial compared telcagepant 280 mg + ibuprofen 400 mg, telcagepant 280 mg + acetaminophen 1000 mg, telcagepant 280 mg and placebo.…”
Section: Telcagepant (Mk-0974)mentioning
confidence: 98%
“…Another Phase II randomized, double-blind, placebocontrolled trial evaluated the efficacy and tolerability of telcagepant when co-administered with ibuprofen or acetaminophen (paracetamol) for the acute treatment of migraine [93]. The trial compared telcagepant 280 mg + ibuprofen 400 mg, telcagepant 280 mg + acetaminophen 1000 mg, telcagepant 280 mg and placebo.…”
Section: Telcagepant (Mk-0974)mentioning
confidence: 98%
“…The first phase II trial compared multiple doses ranging from 25 to 600 mg . Phase III trials confirmed positive results compared to placebo, as well as non‐inferiority of telcagepant 300 mg compared to rizatriptan 10 mg and zolmitriptan 5 mg . The largest of these trials, showed less side effects in the telcagepant group.…”
Section: Introductionmentioning
confidence: 87%
“…Gepants have been tested on patients with coronary artery disease showing good tolerability and no changes on 24‐hour‐ECG . Indeed, there were no cardiovascular side effects in the clinical trials as 5‐HT 1F receptor activation or CGRP receptor inhibition does not result in vasoconstrictor effects . These new options may represent an alternative for migraine patients who do not tolerate triptans’ associated side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic efficacy and tolerability of telcagepant (280 mg) when co-administered with ibuprofen (400 mg) or acetaminophen (1000 mg) was evaluated in a randomized, double-blinded, placebo-controlled trial [26]. Both in co-administration with ibuprofen and acetaminophen, telcagepant resulted more effective than placebo (percentages of patients with 2-h pain freedom 35.2, 38.3, and 10.9%, respectively), but was associated with a higher percentage of adverse events.…”
Section: Calcitonin Gene-related Peptide Antagonistsmentioning
confidence: 99%